A high sensitivity nanosensor of ring resonator with inner stubs for multifunctional sensing. (1st October 2021) - Yan, Shubin; Shao, Zhiquan; Wen, Feng; Yang, Xiaoyu; Guo, Jing; Wu, Xiushan; Hua, Ertian
Abstract: Herein, a novel nanosensor consisting of a ring resonator with two rectangular stubs and a metal–insulator–metal waveguide with two triangular stubs is proposed. By adopting the finite element method, a Fano resonance is found in the transmission spectrum, which results from the coupling between the discrete narrowband mode and the continuous wideband mode. The physical mechanism is analyzed by the normalized magnetic field distribution, and the effects of structural geometric parameters on the transmission characteristics are studied carefully. The results demonstrate that the maximum sensitivity could reach 2660 nm RIU −1 with the corresponding figure of merit of 66.5. The applications of the structure for hemoglobin concentration detection and temperature measurement are discussed, and the sensitivity of the two applications can reach up to 2.524 nm·l g −1 and 0.831 nm °C −1, respectively. The proposed structure with extremely high sensitivity and compactness can provide an excellent case for designing high-performance integrated plasmonic devices.